Abnormal bowel movement frequency increases the risk of rectal cancer: evidence from cohort studies with one million people. Issue 4 (15th April 2020) - Shen, Lin; Li, Chao; Li, Na; Shen, Liangfang; Li, Zhanzhan
Abstract: Previous studies from case–control studies failed to draw reliable conclusions regarding the relationship between bowel movement frequency and the risk of colorectal cancer. To further examine this relationship, we collect the data from cohort studies that make a more accurate estimation. Several online data were searched from inception to February 29, 2020. Ten cohort studies involving 1, 038, 598 individuals were included in our study. The pooled results indicated that a bowel movement of less than once per day was not associated with the risk of colorectal cancer (relative risk (RR)= 1.00, 95% confidence interval (CI): 0.87–1.16, P = 0.950) compared with that of once per day. Compared with a bowel movement frequency of once per day, a bowel movement of more than once per day was also not related to elevated risk of colorectal cancer (RR = 1.04, 95% CI: 0.91–1.19, P = 0.570). The subgroup analyses indicated a low or high bowel movement frequency did not increase the risk of colon cancer (RR = 0.91, 95% CI: 0.80–1.03, P = 0.130). However, an increased frequency of bowel movements increased the risk of rectal cancer (RR = 1.34, 95% CI: 1.19–1.52, P < 0.001). The sensitivity analysis still supports the results. No significant publication bias existed. The data from cohort indicated that less bowel movement frequency was not associated with the risk of colorectal cancer. The frequency of bowel movement affects the risk of rectal cancer.